Transmission error analysis of cycloidal reducers considering crank bearings and output shaft pins - XIA Xiaotian; HAN Ju (Jixie chuandong)
ObjectiveThe transmission error is a critical performance indicator in the design of cycloidal pin wheel reducers. The influence of design parameters for crank bearings and output shaft pins on this error is frequently neglected in existing research. To address the issue, a method for calculating transmission error based on the kinematic and mechanical analysis was introduced, thereby offering theoretical foundation for the optimization of design and the enhancement of performance in cycloidal pinwheel reducers.MethodsFirstly, the motion locus of the meshing point between cycloidal gear teeth and pin teeth was obtained based on the instantaneous motion locus of the cycloidal pin gear mechanism and the meshing interval between them. Subsequently, the design range for the distribution circle radius of crank bearing and output shaft pin was defined. A contact force analysis model for the crank bearing and the output pin was established, and their respective force influences were calculated. Finally, by Masta software, the influence of distribution circle radius on transmission error of cycloidal pinion reducers was analyzed.ResultsThe results show that within the design range for distribution circle radius of the crank bearing and the output shaft pin, the larger values result in smaller transmission errors but greater forces exerted on these components. This study provides valuable insights for designing and optimizing domestic cycloidal reducers.